Transnational Organizing: A Case Study of Contract Workers in the Colombian Mining Industry. (7th January 2014) - Cotton, Elizabeth; Royle, Tony
Abstract This article examines recent organizing successes in the Carbones del Cerrejón coal mine, reversing the organizational crisis of the Colombian mining union, Sintracarbon. Using Wever's concept of 'field‐enlarging strategies', we argue that these events were facilitated by the dissemination of organizing experiences between affiliates of a Global Union Federation, International Federation of Chemical, Energy, Mine and General Workers' Unions (ICEM), which recently merged to form IndustriALL. Additionally, we argue that this articulation between international and national unions, based on the principle of subsidiarity, was facilitated through sustained ICEM educational project activity, providing multiple entry points for Sintracarbon to operationalize its strategy and re‐establish bargaining with multinational employers.